A COMPARATIVE STUDY ON CYBER SECURITY TECHNIQUES USING MACHINE LEARNING - Dr. Gayathri Edamadaka, Dr. Smitha Chowdary.CH, Dr. M. Sobhana, M. V. B. T. Santhi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
In several areas of research, the basic characteristics of machine learning technology such as adaptability, scalability and the ability to react quickly to real and unforeseen problems were introduced. Cyber security is a quickly evolving field that demands tremendous effort, as social media, the Internet, web computing, online banking, the world of smartphones, smart grids, etc. have made unbelievable strides. This paper discusses the use of machine learning in computer defense, including cyber-attack statements targeted at machine learning models, as a defensive and offensive contributor. Machine learning systems are particularly addressed in the case of cyber challenges as intelligent botnets, intelligent spear fishing, and prevention of malware. We also illustrated the use of computer safety learning devices to recognize and prevent vulnerability, track and diagnose malware as well as to determine network threats.